Relationship between anxiety levels and dyspnea among post-COVID-19 patients - Ali Multazam; Diah Nur Pratiwi; Nurul Aini Rahmawati (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Post-corona-virus disease 2019 (Post-COVID-19) syndrome also known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a condition where symptoms arise in COVID-19 patients who have been declared cured according to negative swab results. The level of anxiety can cause it because when anxiety occurs, there is a